Waste disposal by aerobic oxidation - Koch, B.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Waste disposal and odor control are two important problems in pork production. The odor formerly was called the "money smell" has suddenly become "Environmental Pollution." Concentrating many animals in small areas compounds the problem.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Waste disposal; Aerobic oxidation